Estimated thresholds of minimum necessary adherence for effective treatment with direct oral anticoagulants: a retrospective cohort study in health insurance claims data - Wirbka, Lucas; Haefeli, Walter E.; Meid, Andreas (Patient preference and adherence, 2021)
An essential contribution regarding prevention of thromboembolic events in patients with atrial fibrillation is good adherence to direct oral anticoagulants
Gesehen am 10.11.2021